2009
DOI: 10.1007/s00520-009-0715-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy management of cancer-related fatigue: a survey of UK current practice

Abstract: Physiotherapists' management of CRF includes recommending and using exercise and teaching energy-conservation techniques. Therapists recommend and/or use exercise with a variety of cancer populations, across all stages of the disease trajectory, in particular during advanced stages of the disease. Findings show therapists feel their practice is affected by the lack of exercise guidance for the cancer population. CRF management and physiotherapy practice would benefit from further research testing the efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…International studies have identified a need for more health professional education relating to CRF [13][14][15]21]. The most common CRF education received by participants in the current survey was self-directed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies have identified a need for more health professional education relating to CRF [13][14][15]21]. The most common CRF education received by participants in the current survey was self-directed.…”
Section: Discussionmentioning
confidence: 99%
“…Other international surveys of health professionals working in oncology have reported similar findings. Cancer physiotherapists in the UK most commonly promoted exercise and energy conservation [13], while Jordanian nurses believed anaemia correction, sleep, energy conservation and nutrition were the optimal strategies [14]. Oncology doctors and nurses in Turkey predominantly used pharmacological, educational and nutritional interventions [15].…”
Section: Discussionmentioning
confidence: 99%
“…8,29 Canadians living with cancer and health care professionals involved with cancer care have recognized a need for oncology rehabilitation services, 5,11,25-28 yet our survey results suggest that current services are limited in scope and availability.…”
Section: Discussionmentioning
confidence: 82%
“…5,27 Systemic and personal barriers related to establishing oncology rehabilitation programmes have been identified. Systemic barriers include reduced government funding, lack of resources 8,29 and lack of education and training opportunities for physicians regarding the benefits of rehabilitation, as a result of which oncology patients are not referred to rehabilitation professionals for symptom management and treatment as a standard practice. 26,28 Personal barriers to participation in an oncology rehabilitation programme include problems with adherence due to fatigue and other symptoms, as well as families' concerns about energy levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation